2020
DOI: 10.5194/wes-2020-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Model to Calculate Fatigue Damage Caused by Partial Waking during Wind Farm Optimization

Abstract: Abstract. Wind turbines in wind farms often operate in waked or partially waked conditions, which can greatly increase the fatigue damage. Some fatigue considerations may be included, but currently a full fidelity analysis of the increased damage a turbine experiences in a wind farm is not considered in wind farm layout optimization because existing models are too computationally expensive. In this paper, we present a model to calculate fatigue damage caused by partial waking on a wind turbine that is computat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Similarly, if the wake is prominently reaching the falling blade, lower fluctuations in loads can be seen. This was explained nicely by Stanley et al (2020) and is confirmed here with the additional context of positive versus negative yaw angles.…”
Section: Asymmetries and Partial Wakingsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, if the wake is prominently reaching the falling blade, lower fluctuations in loads can be seen. This was explained nicely by Stanley et al (2020) and is confirmed here with the additional context of positive versus negative yaw angles.…”
Section: Asymmetries and Partial Wakingsupporting
confidence: 82%
“…The impact on fatigue and turbine lifetime will be dependent on the frequency of wake steering (Shaler et al, 2022). There is also consensus that imperfect wake steering that exacerbates the presence of partial waking could be even more harmful than not employing wake steering at all (Ciri et al, 2018;Stanley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%